Hubungan riwayat pemberian ASI eksklusif dengan kejadian stunting pada balita usia 24 - 60 bulan di wilayah kerja Puskesmas Sungai Kapih - Lidia Lushinta; Rezki Puspitaningsih; Heni Suryani; Evy Nurachma; Jasmawati Jasmawati (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Currently the incidence of short toddlers or called stunting is one of the nutritional problems experienced by toddlers in the world. One of the causes of the stunting problem is the delay in Early Breastfeeding Initiation (IMD) and non-exclusive breastfeeding. The World Health Organization (WHO) recommends breastfeeding for at least 6 months. Breast milk is a nutritional intake that fits the needs that help the growth and development of children. Children who do not get enough breast milk mean they have poor nutritional intake which can cause malnutrition, one of which can cause the risk of stunting.Objectives: The study aimed to determine the relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers aged 24-60 months in the Sungai Kapih Health Center work area.Methods: The method of this study is observational analytic with a retrospective approach. The number of samples in this study was 72 toddlers. The instrument used to obtain secondary data in this study was the MCH handbook, and the instrument used to obtain primary data in this study was research observation sheets. The data were analyzed using the Fisher Exact test.Results: The results of the study showed that out of 72 toddlers, 36 toddlers experienced stunting, 37 toddlers were not given exclusive breastfeeding and 35 toddlers were given exclusive breastfeeding. Bivariate analysis showed that there was a relationship between the history of exclusive breastfeeding and the incidence of stunting.Conclusion: There is a relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers aged 24-60 months in the Sungai Kapih Health Center work area.